Le cas syrien - Abou Samrah M. (Les incendies de forêt en région méditerranéenne : constitution et utilisation des bases de données, 1995)
In Syria, an average de 1,443 ha is burned per year. Most outbreaks of forest fire occur during the dry period of the year and especially in August, September, October and November. The causes of forest fires are mostly directly related to man.
Séminaire sur les Incendies de Forêt en Région Méditerranéenne, 1993/11/30-1993/12/04, Montpellier (France)